2015
DOI: 10.7575/aiac.ijalel.v.5n.2p.215
|View full text |Cite
|
Sign up to set email alerts
|

Short Films in the EFL Classroom: Creating Resources for Teachers and Learners

Abstract: This study aims to promote the use of films in learning English language in Qassim University, Saudi Arabia. It also tends to explore whether or not the inappropriate use of media like computers and mobiles is the cause behind the learners' low level of proficiency in English. Further, it will shed light on the importance of using multimedia in creating a collaborative and more meaningful learning environment. With the growing use of ICT in education, pedagogies the world over have become more learner centered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Besides, there is evidence that short videos can help students get excited about learning a new language (Madiyoh et al, 2018). Hameed (2016) also reported that even with a small sample size of only fifty students, the study shows that the use of short films in English language education has a significant impact on students' learning results. Irmanda et al (2021) revealed that students became interested in English short films because of the film's audio-visuals.…”
Section: Figure 2 Experimental Class Speaking Score Distributionmentioning
confidence: 82%
“…Besides, there is evidence that short videos can help students get excited about learning a new language (Madiyoh et al, 2018). Hameed (2016) also reported that even with a small sample size of only fifty students, the study shows that the use of short films in English language education has a significant impact on students' learning results. Irmanda et al (2021) revealed that students became interested in English short films because of the film's audio-visuals.…”
Section: Figure 2 Experimental Class Speaking Score Distributionmentioning
confidence: 82%
“…Based on the explanation above, short movies used as learning media to write short story leads to a more interactive language, so that it can effectively help students easily imagine and apply it to written language. In line with this, Hameed (2016) stated that "a visual media in the form of a movie provides an opportunity for a total immersion experience that is impossible to simulate in an environment. Audio visual aspects in movie media have an influence on students' emotional intelligence in learning.…”
Section: Activitiesmentioning
confidence: 99%
“…Education as transformation has transformed methods of learning and teaching, making them more entertaining and productive and YouTube has recently received much attention from scholars and instructors as an instructional tool. Hameed, P. F. M. (2016). The new internet-based language learning modes have long been described as dependable sources.…”
Section: Introductionmentioning
confidence: 99%
“…The rise of the internet gave scholars the opportunity to learn the language through fun and fun activities. According to Halic et al, (2010); (Deng & Yuen, 2010); Hameed (2016); Albahlal (2019) YouTube is an online education platform that makes it easy for students to keep content and push them to learn by means of videos, film and images can improve student's language skills. The challenges face relating to instructors, strategy and facilities most of English teachers are still repetitive in teaching English; instead of teaching materials they give too much attention to the topic of what they teach.…”
Section: Introductionmentioning
confidence: 99%